OPTIMIZATION OF DUTIES OF EMPLOYEES OF PT JALUR NUGRAHA - Nofridayanti Nasution; Rina Filia Sari; Rima Aprilia (Journal of Mathematics and Scientific Computing With Applications, 2021)
Theassignment problem is one part of a linear program which generallyincludes n tasks that must be assigned to m workers, each of whom hasdifferent competencies in carrying out tasks. The Hungarian method isone method that can be used to solve this problem. The purpose of thisstudy is to optimize employee assignments in terms of minimumoperational time in completing work using the Hungarian method.From the results of research using the Hungarian method, timeefficiency is obtained as much as 8 hours if employees in deliveringgoods on the NugrahaEkakurir (JNE) route are placed by the company,namely Ferdi assigned to Medan Tuntungan, Ichsan assigned to MedanSelayang, Riki was assigned to Medan Amplas, Fitriadi assigned toMedan Johor, Irvan was assigned to Delitua, Suryadi was assigned toPatumbak, Edward was assigned to PancurBatu, Citradi was assigned toKutalimbaru, Audi was assigned to Medan Baru and Widiyanto wasassigned to Sunggal.